Indigenous Representational Choices: Results from a Large Qualitative Survey on Māori Electoral Roll Choice - Greaves, Lara Marie; Hini, Rebecca; Overbye, Hannah R.; Brink, Kaylee Grace (Journal of Race, Ethnicity, and Politics, 2025)
Different participatory mechanisms for the representation of Indigenous peoples have been proposed across states. Since their creation in 1867, the Māori electorates in the national Parliament have led to dedicated representation for Māori (Indigenous peoples of New Zealand). However, only half of Māori choose to vote on the Māori roll, the remainder choosing to vote on the General roll, illustrating that roll choice is not based simply on group representation. This survey aimed to ask Māori (N = 1,958) in their own words why they made their roll choice. Through a deductive codebook thematic analysis, a range of codes were constructed around the reasoning behind roll choice. Māori on the Māori roll made their choice because they valued Māori representation; as an expression of their identity; to support the electorates; as a strategic choice; or they had been influenced by others or through education. Those on the General roll felt their roll was the default or a more familiar option; the Māori roll had less of an impact; it was a strategic choice, or they appreciated greater candidate variety; or they valued the smaller geographic electorate size. Some felt Māori no longer needed separate representation or felt less connected to their identity as Māori. The results have implications for both Māori and Indigenous representation through dedicated representational mechanisms.
Keywords: Indigenous; Māori; Māori electorates; Voting, Parties, Parliament; representation; voter enrolment

A Self-Determination Approach to Justifying Indigenous Peoples' Participation in International Law and Policy Making - Charters, Claire (International journal on minority and group rights, 2010)
This paper defends the legitimacy-positive impact of a "contextual-participation approach" to indigenous peoples' participation in international law-making. It argues that indigenous peoples' participation should be substantial where the issue being negotiated at the international level is of considerable interest to indigenous peoples and indigenous peoples have not consented to state representation. The "contextual-participation approach" to indigenous peoples' participation realises the justice in indigenous peoples' claims to remedial efforts to recognise their, mostly lost and historical, sovereignty, and to contemporary and evolving legal, and largely democratic, understandings of self-determination, as expressed, for example, in the UN Declaration on the Rights of Indigenous Peoples. At the same time, it balances indigenous peoples' self-determination entitlements to full participation in international law making, as unjustifiably excluded sovereigns, with contemporary political realities.
Keywords: autonomy; crown law; human rights; indigenous rights; international law; international relations; justice; law; not sure if maori; participation; policy making; political activity; political participation; representation; right wing politics; rights; self-determination; sovereignty; united nations

Opportunities and complexities for Māori and mana whenua representation in local government - Bargh, Maria (Political Science, 2016)
In this article, I outline the existing legislative options available and rationale for M?ori representation in local government. I suggest that the arguments and rationale against M?ori representation have been exacerbated by a lack of clarity around local government?s duties and obligations stemming from the principles of the Treaty of Waitangi. In the second part of this article, I explore more recent arguments by M?ori for representation and involvement in local government decision-making on the basis of being mana whenua, which means to have territorial authority and power associated with the possession and occupation of tribal land. This argument foregrounds specific iwi (tribes) as holding territorial authority and therefore rights to representation and involvement in decision-making sourced in tikanga M?ori (M?ori law), over and above other M?ori who live in that area. I examine in detail the Rotorua District Council?s establishment of the Te Arawa Partnership Board in 2015 and argue that this Board and its first election results provide unique insights into the relationship between Te Arawa people living in and outside the district and has implications for broader conversations about the rights of M?ori living away from their tribal areas.
Keywords: kāwanatanga; local government; mana whenua; political participation; racism; representation; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty principles; voting

Suburban Newspapers’ reporting of Māori news - Rankine, Jenny; Moewaka Barnes, Angela; Borell, Belinda; McCreanor, Tim; Nairn, Raymond; Gregory, Amanda (Pacific Journalism Review : Te Koakoa, 2011)
A content analysis of editorial items about Māori issues and the Treaty of Waitangi in 14 Suburban Newspaper publications in Auckland and Northland found a low proportion of articles about these issues, despite high proportions of Māori resident in several areas served by these publications. Stories included a higher proportion of apparent news releases compared to a national sample of non-daily papers. Māori perspectives came largely from sources representing pan-Māori non-government organisations; Suburban Newspapers used a low proportion of iwi and hapū sources compared with other community papers. Use of te reo Māori was low, and there were no signs of attempts to support readers in learning or increasing their understanding of te reo Māori. This article concludes that Māori and non-Māori readers are poorly served by the poverty of Suburban Newspapers’ reporting of Treaty and Māori issues.
Keywords: media; representation; te reo māori

Anti-Maori themes in New Zealand journalism--toward alternative practice - Moewaka Barnes, Angela; Borell, Belinda; Taiapa, Ken; Rankine, Jenny; Nairn, Ray; McCreanor, Tim (Pacific Journalism Review, 2012)
Gale Academic OneFile includes Anti-Maori themes in New Zealand journalism--toward alt by Angela Moewaka Barnes, Belinda Borell, . Click to explore.
Keywords: health; media; privilege; racism; representation; wellbeing

Theorising representation in the Māori seats: The crucial role of accountability - Nissen, Sylvia; MacDonald, Lindsey Te Ata o Tu (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2017)
The guaranteed Mäori seats are a distinguishing and controversial feature of New Zealand’s democracy. In recent years, a number of reports, commentators and politicians have called for the seats to be abolished on the grounds that they are no longer “needed” in New Zealand’s proportional electoral system. These claims are usually grounded in principles of equality. This paper makes the opposite claim: that principles of equality create convincing and coherent justifications for the Mäori seats. Drawing on feminist theories of representation, particularly the work of Iris Marion Young, Melissa Williams and Anne Phillips, this paper argues that the Mäori seats provide crucial mechanisms of accountability that ensure the fidelity of Mäori representatives to their constituencies. This notion of accountability has been largely absent in debates about the Mäori seats and challenges arguments against the seats that are based solely on perceived “need” relative to proportionate presence.
Keywords: equality; identity; representation